Disasters, Risks and Revelation - Matthewman, Steve. author. aut Link
XI, 204 p.
Keywords: Disasters are part of the modern condition, a source of physical anxiety and existential angst, and they are increasing in frequency, cost and severity. Drawing on both disaster research and social theory, this book offers a critical examination of their causes, consequences and future avoidance.